Production and Characterization of Xanthan Gum with Xanthomonas campestris from Palm Syrup - Heydarzade, H.D.; Gilani, S.L.; Mokhtarian, N.; Alemian, A. (Asian Journal of Chemistry, 2012)
In this work, the effects of reaction temperature on xanthan gum production were investigated. Xanthan gum was produced in batch fermentation by Xanthomonas campestris PTCC 1473 from palm syrup. Fermentations were carried out at different temperatures (20-40 ºC) and 500 rpm with neutral pH. In addition, during experiments, broth viscosities were measured. The results specified that maximum xanthan gum productions were obtained 15.5 g/L from palm syrup at 30 ºC. Furthermore, the chemical structures of the obtained products were evaluated by FTIR spectroscopy.